Prenatal screening and diagnosis of aneuploidy in multiple pregnancies. - Gagnon, Alain; Audibert, Francois (Best Practice & Research: Clinical Obstetrics & Gynaecology, 2014)
Prenatal screening for aneuploidy has changed significantly over the last 30 years, from being age-based to maternal serum and ultrasound based techniques. Multiple pregnancies present particular challenges with regards to screening as serum-based screening techniques are influenced by all feti while ultrasound-based techniques can be fetus specific. Tests currently available tend to not perform as well in multiple compared to singleton pregnancies. Considerations must be given to these variations when discussing and performing screening for aneuploidy in this situation. Prenatal invasive diagnosis techniques in multiple pregnancies bring their own challenges from a technical and counselling point of view, in particular with regards to sampling error, mapping and assignment of results and management of abnormal results. This review addresses these particular challenges and provides information to facilitate care.